Immune correlates of HIV exposure without infection in foreskins of men from Rakai, Uganda - Prodger, J. L.; Hirbod, T.; Kigozi, G.; Nalugoda, F.; Reynolds, S. J.; Galiwango, R.; Shahabi, K.; Serwadda, D.; Wawer, M.J.; Gray, R. H.; Kaul, R. (Mucosal immunology, 2014)
Human immunodeficiency virus (HIV) susceptibility is heterogenous, with some HIV-exposed but seronegative (HESN) individuals remaining uninfected despite repeated exposure. Previous studies in the cervix have shown that reduced HIV susceptibility may be mediated by immune alterations in the genital mucosa. However, immune correlates of HIV exposure without infection have not been investigated in the foreskin. We collected sub-preputial swabs and foreskin tissue from HESN (n¼20) and unexposed control (n¼57) men undergoing elective circumcision. Blinded investigators assayed swabs for HIV-neutralizing IgA, innate antimicrobial peptides, and cytokine levels. Functional T-cell subsets from foreskin tissue were assessed by flow cytometry. HESN foreskins had elevated a-defensins (3,027 vs. 1,795 pgml 1,P¼0.011) and HIV-neutralizing IgA(50.0 vs. 13.5%ofmen,P¼0.019).Foreskin tissue from HESN men contained a higherdensityofCD3 T cells (151.9 vs. 69.9 cellsmm 2, P¼0.018), but a lower proportion of these was Th17 cells (6.12 vs. 8.04%of CD4 Tcells, P¼0.007), and fewer produced tumor necrosis factor a (TNFa) (34.3 vs. 41.8% of CD4 Tcells, P¼0.037; 36.9 vs. 45.7%of CD8 T cells, P¼0.004). A decrease in the relative abundance of susceptible CD4 T cells and local TNFa production, in combination with HIV-neutralizing IgA and a defensins, may represent a protective immune milieu at a site of HIV exposure.
Keywords: Immune correlates; HIV; Infection; Foreskins of men; Uganda